Lambda c(+), Sigma(c), and Lambda(b) hypernuclei in the quark-meson coupling model - Tsushima, K.; Khanna, F. C. (Iop Publishing Ltd, 2004)
Charmed (and bottom) hypernuclei are studied in the quark-meson coupling (QMC) model. This completes systematic studies of charmed (Lambda(c)(+), Sigma(c), Xi(c)), and Lambda(b) hypernuclei in the QMC model. Effects of the Pauli blocking due to the underlying quark structure of baryons, and the Sigma(c)N-Lambda(c)N channel coupling are phenomenologically taken into account at the hadronic level in the same way as those included for strange hypernuclei. Our results suggest that the Sigma(c)(++) and Xi(c)(+) hypernuclei are very unlikely to be formed. while the Lambda(c)(+), Xi(c)(0) and Lambda(b) hypernuclei are quite likely to be formed. For the Sigma(c)(+) hypernuclei, the formation probability is non-zero, though small. A detailed analysis is also made about the phenomenologically introduced Pauli blocking and channel coupling effects for the Sigma(c)(0) hypernuclei.